2008
DOI: 10.1016/j.ijrobp.2008.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Automatic Anatomy Segmentation Algorithm on Repeat or Four-Dimensional Computed Tomography Images Using Deformable Image Registration Method

Abstract: Purpose-Auto-propagation of anatomical region-of-interests (ROIs) from the planning CT to daily CT is an essential step in image-guided adaptive radiotherapy. The goal of this study was to quantitatively evaluate the performance of the algorithm in typical clinical applications.Method and Materials-We previously adopted an image intensity-based deformable registration algorithm to find the correspondence between two images. In this study, the ROIs delineated on the planning CT image were mapped onto daily CT o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 41 publications
2
84
0
Order By: Relevance
“…Some of the treatment beams may pass through the CT couch, therefore the CT data representing the imaging couch were replaced with a digital treatment couch using in-house software to properly account for beams that intersected the treatment couch. 19 Contours from the original planning CT image were propagated to the treatment-time image using in-house deformable image registration software [20][21][22] to delineate the patient anatomy at the time of treatment for dose-volume histogram (DVH) calculations. The algorithm was assessed for use in automatic contour propagation for repeat CT and 4DCT imaging and found that interfraction accuracy of 0.4 mm mean absolute surfaceto-surface distance and intrafraction accuracy of >98% volume overlap was achievable when compared to the physicianmodified contours.…”
Section: Iia Patient Data Setmentioning
confidence: 99%
“…Some of the treatment beams may pass through the CT couch, therefore the CT data representing the imaging couch were replaced with a digital treatment couch using in-house software to properly account for beams that intersected the treatment couch. 19 Contours from the original planning CT image were propagated to the treatment-time image using in-house deformable image registration software [20][21][22] to delineate the patient anatomy at the time of treatment for dose-volume histogram (DVH) calculations. The algorithm was assessed for use in automatic contour propagation for repeat CT and 4DCT imaging and found that interfraction accuracy of 0.4 mm mean absolute surfaceto-surface distance and intrafraction accuracy of >98% volume overlap was achievable when compared to the physicianmodified contours.…”
Section: Iia Patient Data Setmentioning
confidence: 99%
“…It has been a research forefront to combine image registration with image segmentation, although most research focus on using deformable image registration to assist adaptive segmentation (or active contouring) (Vernuri, et al, 2003, Barder & Hose, 2005, Shekhar, et al, 2007, Wang, et al, 2008. The foundation of the hybrid approach to use segmentation to www.intechopen.com…”
Section: Future Directions Of Volumetric Image Registrationmentioning
confidence: 99%
“…Atlas segmentation 7 , 8 , 9 , 10 , 11 , 12 has emerged recently as an alternative to increase accuracy, compared to standard segmentation techniques, by incorporating both spatial information and voxel classification schemes into the algorithm's design. In a fundamental paradigm shift, the atlas‐based approach relies on the existence of a map between a reference image volume (called an atlas) in which structures of interest have been segmented and validated by an expert, and the image to be segmented, called the subject.…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of techniques based on manual landmark‐based registration, (23) on a BSpline 17 , 24 registration using a multimodality metric (25) or a demons approach (12) have been used to generate the correct map for these anatomic sites. For other sites, atlas segmentation has been proposed for clearly demarcated structures.…”
Section: Introductionmentioning
confidence: 99%